2006
DOI: 10.1182/blood-2005-12-4916
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic application of flow cytometric characteristics of CD34+ cells in low-grade myelodysplastic syndromes

Abstract: were analyzed using 4-color flow cytometry (FCM). We objectively determined reference ranges of 13 parameters related to CD34 ؉ cells with data from controls. InLGw/oRS patients, various abnormalities of CD34 ؉ cells-eg, decrease in CD34 ؉ B-cell precursors, aberrant expression or overexpression of various antigens on CD34 ؉ myeloblasts-were observed. We constructed a reproducible, flow cytometric scoring system for LGw/oRS diagnosis. High scores were observed in 16 of 27LGw/oRS patients, regardless of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
175
0
20

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(202 citation statements)
references
References 30 publications
7
175
0
20
Order By: Relevance
“…The reliability of the adopted gating strategy was previously reported, 15,19,20 and was verified in addition in 30 patients enrolled in this study (Online Supplementary File S1).…”
Section: Flow Cytometry Studies On Bone Marrow Cellsmentioning
confidence: 79%
See 3 more Smart Citations
“…The reliability of the adopted gating strategy was previously reported, 15,19,20 and was verified in addition in 30 patients enrolled in this study (Online Supplementary File S1).…”
Section: Flow Cytometry Studies On Bone Marrow Cellsmentioning
confidence: 79%
“…[14][15][16] Consistent immunophenotypic aberrations reported in the CD34 + cell compartment in MDS are: an increase of the myeloid-committed CD34 + population, 10,15,17 a decrease of B-cell progenitors, 15,18 co-expression of stem cell-and late stage-myeloid antigens, expression of lymphoid antigens 7,8,11 and abnormal CD45 expression. 15 We previously reported that data for three of these parameters (percentage of myeloblasts, percentage of Bcell progenitors, and myeloblast CD45 expression) together with the evaluation of side scatter (SSC) on granulocytes are reproducible in many laboratories when measured by methods ensuring little inter-operator variability, 19,20 and when combined are able to differentiate correctly patients with MDS from patients with non-clonal cytopenia. 20 To be implementable in clinical practice, an extensive validation of this approach is required.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…When the morphological dysplastic features are mild or even absent and PB cytopenias are persistent the diagnosis is termed idiopathic cytopenias of undetermined significance (ICUS) (Valent et al , 2012; Bejar & Steensma, 2014). Evaluating myelodysplastic features using flow cytometry is a growing field of interest and highly sensitive multicolour immunophenotypic profiling and accompanying scoring systems have proven useful in MDS, both in diagnostic and prognostic terms (Ogata et al , 2006; van de Loosdrecht et al , 2008). …”
mentioning
confidence: 99%